Fundamental of Entrepreneurship ENT300: Planet Satay Cafe/ Azria Ali Yaman ... [et al.] - Ali Yaman, Azria; Mohd Mansoor, Siti Noor Aisyah; Julayah, Alhafizah; Asmadi, Mohd Asri; Mohd Zainuddin, Azimah (2010)
In business, administration consists of the performance or management of transactions and other matters, and the making and the implementing of major decisions. Administrations can be defined as the universal process of organizing people and resources efficiently so as to , direct activities toward common goals and objectives. Administrations also can serve as the title of General Manager who reports to corporate boards of directors. In some organizational analysis, administration is viewed as one of the important management. It consists of a well-organized hierarchy management which include from the top level management to the supporting staff. Administrations will involves directly in advocating the procedures regarding the employment, development and welfare of the personnel in the organization. Planet Satay Café aim to produce a delicious and sensuous delight sate and to be number sate place in Sarawak. Besides, we will ensure that our customer is our priority.